Improvised Skeletal Traction in the Management of Ballistic Femoral Fractures. Issue 3 (1st September 2009) - Boyd, MC; Mountain, AJC; Clasper, JC
Abstract : Penetrating limb injuries are common during conflict, and in many there will be an associated fracture. Treatment of ballistic femoral fractures would usually be with by intramedullary nail; however, within the resource-constrained environment during conflict this is rarely possible. This report illustrates what can be achieved at a Role 2 facility to provide skeletal traction with the equipment and skills available. We discuss the history of skeletal traction and its use in ballistic femoral fractures, and believe that skeletal traction is still a valuable technique that we shouldn’t ignore. Military surgeons should be able to use skeletal traction to manage ballistic femoral fractures in the spartan environment of a deployed forward hospital.